Adapting business framework conditions to deal with disruptive technologies in Denmark - Hermansen, Mikkel (OECD Economics Department Working Papers, 2019)
Danish firms are close to the technological frontier compared to other OECD countries, making the introduction of new - potentially disruptive - technologies key to boost productivity growth. Despite a high level of digitalisation and good framework conditions, aggregate productivity growth in Denmark has been only average compared to other advanced OECD countries and lags behind in less knowledge-intensive service industries. Policy needs to embrace innovative technologies by leaning against attempts to discourage or exclude them and by tackling unintended or outmoded obstacles in legislation and regulation. Analysis based on Danish firm-level data suggests that digital adoption through investment in ICT capital increases firm productivity and contributes to business dynamics and firm growth. Improving economic incentives for such investment as well as facilitating adoption of new business models require a shift of taxation away from capital and labour income. Ensuring supply of the right skills and maintaining effective upskilling will help workers cope with disruptive changes and ensure that economic growth benefits all